Produção e manejo de Adesmia latifolia (SPRENG.) VOG. - Menezes, Fernando Pereira de (2011)
The study was conducted in three stages, assessing the species Adesmia latifolia (Spreng.) Vog. with the aim of increasing knowledge of Adesmia responses regarding the most appropriate methods of overcoming seed dormancy, seed inoculation and production and forage quality in relation to climatic factors. The first stage was conducted at the Laboratory of Seeds Analysis FAEM/UFPEL in Pelotas, the other in the CCR/URCAMP in Bage-RS. In the work of scarification were evaluated with thermal and chemical methods to count only 14 days after sowing. Regarding the assessment of inoculant was used the following treatments: control, Bradyrhizobium spp. Rhizobium leguminosarum bv. trifolli (white clover), Rhizobium leguminosarum bv. trifolli (red clover) and Rhizobium loti (birdsfoot trefoil) in a greenhouse. The third study, conducted in the field, we evaluated the production of dry matter and forage quality, protein digestibility and in vitro. In the first work considering the three variables (normal seedlings, hard seeds and dead), the results showed that the method of soaking in hot water was more efficient in breaking dormancy of seeds of Adesmia latifolia, with emphasis on immersion in hot water at 40°C for three minutes, for issues of safety and economy. In the second study produced the highest dry matter were obtained with Bradyrhizobium spp. and Rhizobium loti, respectively, the same happened in relation to the efficiency of inoculation, with the latter being easily accessible shopping. In the third study concluded that the dry matter production is concentrated in october/november with 88% of total annual crude protein and in vitro while maintaining during the cycle with high levels.